Effect of vernalisation and azacytidine on the DNA methylation level in wheat (Triticum aestivum L. cv. Mv 15) - Horváth, Eszter (Acta Biologica Szegediensis, 2002)
The aim of the research was to examine the changes occurring during vernalisation in the 5-methylcytosine content of the DNA in a winter wheat variety with a short vernalisation requirement after treatment with 5-azacytidine, and to determine the correlation between the quantity of 5-methylcytosine and flowering. The results indicated that both vernalisation treatment and 5-azacytidine, a compound causing demethylation, reduced the methylation of the DNA in the winter wheat variety Mv 15. The data also proved that although the 5-azacytidine treatment reduced the methylation of the DNA in unvernalised plants, this in itself was not sufficient to induce flowering.